PENINGKATAN HASIL TANAMAN OKRA (Abelmoschos esculentus L Moench) DENGAN KOMPOSISI MEDIA TANAM DAN PUPUK CAIR HAYATI - Teguh Riyanto; Mohamad Ihsan; Tri Pamujiasih (PROSEDING, 2022)
Thiszstudyxwaseconducted tordeterminesthetincrease in6yield ofdokraj(Abelmoschus esculentuseLrMoench) plants5with theycomposition ofgplanting mediayand biologicalk liquidofertilizer.iThiseresearchswasyconducted in December 12018 ytogMarch%2019, in5Duren Hamlet,EWonorejoZVillage, KalijambeYDistrict, SragenKRegency atKan altitudeLbetween 100 mIabove seaYlevel. This5research isFa factorialSexperiment with%aPcompletely randomizedIdesign (CRD)Apattern consistingHof twoItreatmentS factors. Theyfirst9treatment factordis theycomposition of0the plantinge mediumy(M) whichiconsists ofo4 levelsy(M1 = oneysoil withoutomanureiand huskycharcoaly= 1: 0: 0, M2 = one soil + one manure + one husk charcoal = 1: 1 : 1, M3 = one holdy+ two manurey+ one husk charcoal = 1: 2: 1, M4 = one soili+ three manure + one husk charcoal = 1: 3: 1). Theysecond treatmentkfactor,uthe concentrationuof biologicaliliquidafertilizer (P) consistingyof54 levels (P1 = 08ml / lswater, P2 = 21ml / l1water, P3 = 3oml / liwater, P4 = 4 ml / l water). Parameters observed included plantyheight, numberpofileaves, numberyofa fruits, weight ofufruitiper plant, weighteof freshystover. Theyresults showedythatytheytreatmentpof thei compositionyofithe plantinga medium (M) had veryi significantyeffectuonythe parameters1of plantfheight, numberuofeleaves, number of5fruits, weighteof fruitmper plant andoweight ofufresh stover, while the concentration of biological liquid fertilizer (P) was not significantly different and (MxP) gives interactions not significantly different. Theeresults of thewaverage observations of parameters obtained by the best plant height found in M2 planting media with an average height (121.82) cm, the number of leaves is good ineM3 (28.46) and M4 planting media (28.13) , the weight of fresh stover was found in M3 (415.04) g and M4 (404.71)gomedia, theohighest numberkof fruitsipereplant was found in M3 (16.94) and M2 (16.80), and heavy planting media. fruit per best plant in M3 planting media (452.95)g. Theiresults ofithe studyuwere obtained fromythe whole treatmentiof the best compass media on media composition (M3 = one soil + two manure + one rice husk charcoal = 1: 2: 1) which gave the best results on the parameter numberyof leaves (28.46), numberkof fruits peroplant (16.94), weight offfruit periplant (452.95) gr, heavy berangkasan (415.04) gr. While the lowest results on the planting medium (M1) onithe parameters offplant height (63.30) cm, number ofeleaves (14.42), numbersofyfruits (3.79), weightyof fruiteper plant (33.57) gr and weightiofufresh stover (29.75) gr. Keywords: okra, biological liquid fertilizer, planting media